2022
DOI: 10.1113/ep089404
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 coagulopathy – what should we treat?

Abstract: New Findings What is the topic of this review?Overview of the coagulation abnormalities, including elevated D‐dimers widely reported with COVID‐19, often labelled as COVID coagulopathy. What advances does it highlight?The review highlights the changes in bronchoalveolar haemostasis due to apoptosis of alveolar cells, which contributes to acute lung injury and acute respiratory distress syndrome; the pathophysiological mechanisms, including endothelial dysfunction and damage responsible for thrombosis of pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 104 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…Autoptic studies on COVID-19 deaths have shown a great prevalence of lung microvascular thrombosis: in light of the observed disease-induced coagulopathy, many studies have described elevated D-dimer levels at admission as an independent predictor of negative disease evolution and in-hospital COVID-19 mortality [ 38 , 44 , 45 , 48 , 49 , 50 ]. On the other hand, recent studies have highlighted that D-dimer levels below the standard or age-adjusted threshold in SARS-CoV-2 patients referred to the emergency department could be considered as a predictor of a low risk for pulmonary embolism complications [ 51 , 52 ].…”
Section: Currently Validated Biomarkers In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Autoptic studies on COVID-19 deaths have shown a great prevalence of lung microvascular thrombosis: in light of the observed disease-induced coagulopathy, many studies have described elevated D-dimer levels at admission as an independent predictor of negative disease evolution and in-hospital COVID-19 mortality [ 38 , 44 , 45 , 48 , 49 , 50 ]. On the other hand, recent studies have highlighted that D-dimer levels below the standard or age-adjusted threshold in SARS-CoV-2 patients referred to the emergency department could be considered as a predictor of a low risk for pulmonary embolism complications [ 51 , 52 ].…”
Section: Currently Validated Biomarkers In Clinical Practicementioning
confidence: 99%
“…Even if the involvement of D-dimers in COVID-19 pathophysiology is not fully understood, it has been hypothesized that its increase is a direct consequence of microthrombosis in lung and kidney capillaries, as it should be considered that thromboinflammation is one of the host defense mechanisms commonly activated in response to viral, bacterial, and fungal pathogens [ 38 , 45 , 48 , 49 ].…”
Section: Currently Validated Biomarkers In Clinical Practicementioning
confidence: 99%
“…The severe life-threatening manifestations of influenza and COVID-19 are associated with a dysregulated immune response and hyperproduction of proinflammatory cytokines and chemokines such as interleukin (IL)-1b, IL-6, tumor necrosis factor (TNF)-a, interferon (IFN)-c inducible protein-10, monocyte chemoattractant protein-1, and IL-8 [20][21][22][23][24][25]. The unchecked immunological/inflammatory alterations lead to further tissue damage [20][21][22][23][24][25], in addition to that caused by virus replication alone, and to increased risk of thrombosis [26] not responding to anticoagulation alone [27]. Targeting the immunological/inflammatory dysfunction with glucocorticoids, Janus kinase inhibitors, and humanized monoclonal antibodies against the IL-6 receptor (IL-6R) [28][29][30], in addition to providing maximal supportive therapy [31], significantly reduces the risk of respiratory failure and death in hospitalized patients with severe COVID-19-associated pneumonia, hypoxia, and evidence of systemic inflammation, but the residual numbers of individuals requiring IMV and dying because of respiratory failure remain elevated in the clinical trial setting [28][29][30] and in clinical practice [32].…”
Section: Rationale For the Potential Use Of Mscs And Msc-derived Secr...mentioning
confidence: 99%
“…This statement is from a subset of pediatric patients who presented with multiple organ failure and severe inflammation and were diagnosed as SARS-CoV-2 positive. One of the most major complications of COVID 19 is the arterial hypoxemia, thus affecting the lung compliance which could require mechanical ventilation (6,7) . Acid base imbalance is a frequent association with patients who suffer from serious viral illnesses including COVID-19 (8) .…”
Section: Introductionmentioning
confidence: 99%